If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.6t = 0.9 + 0.4t Solving 0.6t = 0.9 + 0.4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-0.4t' to each side of the equation. 0.6t + -0.4t = 0.9 + 0.4t + -0.4t Combine like terms: 0.6t + -0.4t = 0.2t 0.2t = 0.9 + 0.4t + -0.4t Combine like terms: 0.4t + -0.4t = 0.0 0.2t = 0.9 + 0.0 0.2t = 0.9 Divide each side by '0.2'. t = 4.5 Simplifying t = 4.5
| 3(4z-7)=21+12z | | h/2=13.44 | | 7x/7=x | | 2(10*2)-4(5*2)= | | y=-8+92 | | 31-(2x+4)=2(x+6)+x | | n-4-2n=n+6-8+10 | | 83-2x=66 | | In(5*y^2)=3+In(x) | | X-3-4=15+8x-3+2 | | In(5*y^2)=3+In(n) | | In(5*x^2)=3+In(n) | | -5=8x-29 | | 9s+2t-4s= | | In(5*x^2)=3+In(a) | | -5=-3x-17 | | f(x)=x^2+4x+17 | | X=13+(7x-13) | | 24x-7-13x+4=25x-8-14x+16 | | v/9.8=23 | | 2(10t)=30+10 | | W=1/6v | | -5=2x-23 | | 4/(-1)=n | | 10x-6=10x-20 | | 5(x-20)=190 | | m/π=7.3 | | x-2=-6x-18 | | 5.8m=.5 | | 5(x-10)-3=6x-46 | | 2-1+4+4-3= | | x-2=6x+18 |